Medieval German Lyric Verse in English Translation - Thomas, J.W (UNC Studies in the Germanic Languages and Literatures, 1968)
This anthology contains representative selections from the verse of Minnesingers, nuns, priests, goliards, Spielleute, middle-class singers, and noblemen from the twelfth to the fifteenth century together with historical background, biographical sketches, and comments on individual poems. At the time of its original publication it was the largest such collection in English.